1996
DOI: 10.1111/j.1365-2885.1996.tb00078.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of the pharmacokinetics and tissue residues of an oral trimethoprim/sulphadiazine formulation in healthy pigs

Abstract: Twenty-six healthy female pigs weighing 19.5-33 kg were used in three separate experiments. The animals were fed individually twice a day. Trimethoprim/sulphadiazine (TMP/SDZ) formulation was added to feed in the amount of 6 mg/kg bw (TMP) and 30 mg/kg bw (SDZ). TMP and SDZ concentrations in blood plasma, muscles, liver and kidneys were measured. Pharmacokinetic parameters show that the absorption of TMP from the alimentary tract in pigs is faster than the absorption of SDZ, and the elimination of TMP is slowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
4
11
0
Order By: Relevance
“…As shown by Nielsen and Gyrd‐Hansen (1994) and Garwacki et al . (1996), the absorption phase in fed pigs is somewhat prolonged and shows a large individual variation.…”
Section: Pharmacokinetic Parameters After IV (Trisuprime 24%) and supporting
confidence: 93%
See 2 more Smart Citations
“…As shown by Nielsen and Gyrd‐Hansen (1994) and Garwacki et al . (1996), the absorption phase in fed pigs is somewhat prolonged and shows a large individual variation.…”
Section: Pharmacokinetic Parameters After IV (Trisuprime 24%) and supporting
confidence: 93%
“…Trimethoprim, which has a high volume of distribution, passes rapidly from the plasma into tissues. Therefore, the TMP/SDA ratios in various tissues differ from those in the plasma (Garwacki et al ., 1996). To achieve the optimal ratio of 1:20 in plasma, a pharmaceutical dosage form which contains TMP and SDA in a 1:5 ratio was chosen.…”
Section: Pharmacokinetic Parameters After IV (Trisuprime 24%) and mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in other species, such as swine (Nielsen and Rasmussen, 1975a,b;Garwacki et al, 1996), dogs and cats (Craig and White, 1976;Sigel et al, 1981), horses (Brown et al, 1983;Bogan et al, 1984;Van Duijkeren et al, 1994a, Gustafsson et al, 1999, poultry (Lo« scher et al, 1990;Batzias et al, 2000;Baert et al, 2003), rabbits (Ladefoged, 1977) and ¢sh (Nouws et al, 1993), have also been performed. All investigators clearly reported higher values of volume of distribution (V) and clearance (Cl), together with a substantially shorter elimination half-life for TMP, compared to SDZ.…”
Section: Introductionmentioning
confidence: 95%
“…To our knowledge, there is a lack of information at present regarding the pharmacokinetic behavior of SDZ and TMP in mandarin fish. Several pharmacokinetic studies of SDZ, TMP, or both have been conducted in other species such as chickens (Baert et al ., ), cattle and calves (Shoaf et al ., ; Kaartinen et al ., ), ponies and horses (Van Duijkeren et al ., , ), dogs (Sigel et al ., ), pigs (Baert et al ., ; Garwacki et al ., ), and ostrich (Abu‐Basha et al ., ). This study evaluates the pharmacokinetic and residual parameters of SDZ and TMP and discusses their rational ratio in mandarin fish for well treatment of bacterial diseases.…”
Section: Introductionmentioning
confidence: 99%